Model Literasi Berbasis Entrepreneurship dalam Peningkatan Ekonomi Produktif Perempuan Istri Nelayan Tradisional - Arbarini, Mintarsih; Rifai, Achmad; Mulyono, Sungkowo Edy (Journal of Nonformal Education and Community Empowerment, 2018)
This study aims to develop a model of entrepreneurship-based literacy to improve productive economy for the wives of traditional fishermen. This literacy model is a solution in empowering the wives of traditional poor fishermen through literacy learning (reading, writing, arithmetic, speaking and listening) based on life skills and entrepreneurial skills. Entrepreneurship-based literacy models are designed so that women and fishermen's wives are able to face life's problems through life skills-based literacy learning and entrepreneurship as a solution to improving the family economy. This research approach uses research and development. The study was conducted on poor fishermen's wife women in Tugu District, Semarang City, Central Java. Data collection instruments and techniques used interview, observation, and documentation guidelines and focus group discussions (FGD). The research subject was the wife of the fisherman. The data analysis technique was carried out by analyzing the data from interviews, observations, and documentation in a qualitative and development descriptive manner. The results showed that: (1) the socio-economic and education of the fishermen's family were in poor condition, they were still in poor socio-economic conditions. 3) Efforts made by the wives of fishermen to meet the economic needs of their families by relying on existing income for their daily needs. 3) Entrepreneurship-based literacy education is based on fulfilling the interests and needs of the wives of traditional fishermen, and includes activities that help them to apply new abilities and skills acquired, in order to improve their quality and standard of living. The literacy model developed emphasizes life skills related learning needs that consist of a variety of vocational skills and also emphasizes the development of work motivation, modern attitudes, and other life skills that can arouse entrepreneurial spirit so that it can improve productive economies.